Species Diversity, Conservation Status, and Policy Gaps of Landed Elasmobranchs at Ujungbatu Fish Landing Site, Jepara in Support of SDG 14 (Life Below Water) - Azzahra Aino Javidani; Yuniarti MS; Muhammad Ichsan; Titin Herawati; Yudi Nurul Ihsan (Jurnal Penelitian Pendidikan IPA, 2026)
This preliminary study aimed to identify species diversity and assess the conservation status of elasmobranchs landed at Ujungbatu Fish Landing Site (TPI Ujungbatu), Jepara, Central Java. Primary data were collected from July to August 2025 using purposive and opportunistic sampling methods.  A total of 24 species were recorded - eight shark species and 16 ray species - from a total of 112 specimens. Conservation assessment revealed critical urgency:  36.61% of specimens (n=41) belonged to Critically Endangered (CR) species, including Sphyrna lewini, Aetomylaeus vespertilio, and three Rhynchobatus species from the family Rhinididae. Endangered (EN) and Vulnerable (VU) species collectively comprised 41.96% (n=47), while the remaining 21.43% (n=24) were Near Threatened or Least Concern. Overall, 78.57% of landed elasmobranchs belonged to threatened categories (CR+EN+VU). A significant policy gap was identified: only 42.86% of specimens were covered by CITES Appendices, while several Dasyatidae species classified as EN or VU remain inadequately regulated under international trade mechanisms, despite recent CoP19 (2022) listings. These findings underscore the urgent need for strengthened monitoring, species-specific management strategies, and improved harmonization between national policies and international conservation commitments to support SDG 14.